The Anthropology of Digital Activism: The Role of Youth in Peacebuilding through Social Media - Dr. Shakeela Ibrahim (Indus Journal of Social Sciences, 2025)
This paper focuses on digital anthropology, a field that is gaining increasing importance in the digital world. People use technology for different purposes, such as making life easier. They utilise media platforms to resolve problems, acquire knowledge, and engage with their societies. This paper examines the role of youth in peacebuilding through social media. This research demonstrates that social media can serve as an effective platform that fosters democratic conversation and freedom of speech. However, due to the unregulated nature of the internet and social media, individuals lacking ethical principles and professionalism can exploit these platforms to spread misinformation. This kind of misinformation can result in the disruption of peace and trigger acts of violence. This study examines the relationship between social media and conflict prevention and peacebuilding, as well as how youth utilise social media for advocacy and activism. This type of motivation drives them and involves digital peacebuilding in their societies. This research covered the locality of Islamabad Universities to analyse youth behaviour for peacebuilding through media. A qualitative technique has been used to collect data from 100 respondents. A thematic analysis was used to analyze the data. Three key informants were selected through social media channels to discuss their experiences and share their perspectives on the role of youth in peacebuilding. The research indicated that over 82 percent of those surveyed were active on social media, and the rest used social media to get information. A significant portion of the respondents had between 101 and 800 social media friends. Additionally, the research found that respondents utilised traditional media, such as television and newspapers, to enhance peace in society by obtaining information from social media. This research revealed that if the government were to regulate social media, users would primarily utilize it for social interactions.